GERAKAN KESETARAAN GENDER ISLAM DI INDONESIA - Saifuddin Saifuddin; Fatmawati Norma Sari (Cendekia, 2019)
Gender equality movement is continuation of gender equality study. Although some religious exegesis -moreover those are done by classic muslim religious leader- gender biased up to now, study of religious texts done by muslim feminist was inspiring development of gender equality movement.Nowadays gender equality movement in Indonesia is in fourth level. In this level the role of muslim feminists is more dominant. Indeed, next generations are growing up more. It shows that gender equality is part of islamic teachings.